Los desvíos de Calibán: emancipación y lenguaje en Reinaldo Arenas - Maccioni, Laura (Diálogos Latinoamericanos, 2007)
During the 1960s and ’70s, the pressure of politics over cultural practices had crucial effects on literature. One of them was the rereading of foundational texts that had, historically, provided the metaphors to interpret the past, and, consequently, the meaning of the present. The colonial allegory displayed by Shakespeare’s The Tempest was one of these texts. In 1972, Roberto Fernández Retamar recovered the opposite pair of Calibán and Próspero in his essay Calibán. However, contrary to Rodo’s Ariel reading of the drama, Retamar made Calibán a symbol of the imminent emancipation of the continent. Nonetheless, in this (in) version of Shakespeare’s story, Calibán also remained a slave, as he was perpetually committed to demonstrate the Truth of an essential entity, the People of Latin America. This paper discusses some other ways of imagining Caliban’s emancipation. I will focus on Reinaldo Arena’s re-writing of emancipation in “El Central” and the short story “El reino de Alipio”.